Comparison of tolerance and biosorption of three trace metals (Cd, Cu, Pb) by the soil fungus Absidia cylindrospora. (April 2018) - Albert, Quentin; Leleyter, Lydia; Lemoine, Mélanie; Heutte, Natacha; Rioult, Jean-Philippe; Sage, Lucile; Baraud, Fabienne; Garon, David
Abstract: Trace metals cause deterioration of the soil and constitute a major concern for the environment and human health. Bioremediation could be an effective solution for the rectification of contaminated soils. Fungi could play an important role in biodegradation because of the morphology of their mycelium (highly reactive and extensive biological surface) and its physiology (high tolerance to many stresses, production of enzymes and secondary metabolites). Fungi can effectively biosequestrate, or biotransform many organic and inorganic contaminants into a non-bioavailable form. This experiment was designed to evaluate the tolerance and the biosorption abilities of the fungus Absidia cylindrospora against three trace metals: Cadmium (Cd), Copper (Cu), and Lead (Pb). Firstly, the tolerance of the strain was evaluated on metal-enriched malt extract agar (MEA). Secondly, the strain was exposed to trace metals, in a liquid malt extract medium. After 3 or 7 days of exposure, the quantities of absorbed and adsorbed metals were measured with Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Biomass production and pH evolution were also evaluated during the test. Our experiment revealed differences between the three metals. In agar medium, Cd and Pb were better tolerated than Cu. In liquid medium, Cd and Pb were mostly absorbed whereas Cu was mostly adsorbed. A. cylindrospora biosorbed 14% of Cu, 59% of Pb and 68% of Cd when exposed for 3 days at 50 mg L −1 . Highlights: Absidia cylindrospora was able to biosorb 68% of Cd, 59% of Pb and 14% of Cu after 3 days of exposure at 50 mg L −1 . Cd and Pb were mostly absorbed, whereas Cu was mostly adsorbed. Cd and Pb inhibited fungal biomass production, but Cu did not. pH decreased after 3 and 7 days of Pb exposure and after 7 days of Cd exposure. pH did not change on exposure to Cu.